A Study to Assess the Awareness of the Breast Cancer Screening Among Teacher Training Students in Selected Teacher Training Institutions at Mysuru with the View to Conduct Educational Program - Sunitha P.S.; Rashmi P. (International Journal of Oncological Nursing and Practices, 2023)
Background: Cancer is one of the major causes of death both in developed and developing countries. Breast cancer is defined by the uncontrollable proliferation of cells within the breast, encompassing different forms of cancer that impact the breast tissue. The majority of breast cancer cases manifest as painless lumps, while a smaller percentage may exhibit additional symptoms. Breast cancer is amenable to almost complete care if detected in its early stages. Breast self-examination, clinical breast exam and mammography are the preventive techniques to reduce Breast Cancer mortality and morbidity. Breast Self-Examination is a useful and non-expensive self-care activity which can be crowed out monthly by women; this will help to detect malignancy in its early stage which can save lives. Aim: The aim of this study is to assess the knowledge regarding breast cancer screening among teacher training students in selected teacher training institutions of Mysuru. Methods: This study employed a descriptive survey design to investigate the research questions. The study took place in teachers training colleges situated in Mysuru. The content validity of the questionnaire was evaluated by five experts, and the reliability of the structured knowledge questionnaire was established through the split-half method. The study sample of 60 participants was selected using a non-random convenience sampling technique. The data was gathered through the administration of a structured knowledge questionnaire specifically designed to assess participants' understanding of breast cancer screening. The data was analysed with help descriptive and inferential statistics. Result: The result of study reveals that 44 (73.44%) Teacher training students are in the age group of 15–20 years, 16 (26.66%) are in the age group 20–25 years, 07 (11.66%) teacher training students are from Muslim religion, majority (53 (88.44%)) teacher training students are from Hindu religion, 14 (23.44%) teacher training students did not know about breast cancer screening, majority (46 (76.66%)) knew about the breast cancer screening, 05 (8.44%) had family history of breast cancer, majority (55 (91.66%)) did not have family history of breast cancer, 20 (33.44%) did not have previous exposure to any educational programme regarding breast cancer, majority (40 (66.76%)) had previous exposure to educational programme regarding breast cancer screening; 5% of them had poor knowledge, 46.66% had average knowledge and 48.33% of them had good knowledge. A noteworthy correlation was observed between the knowledge scores of teacher training students in relation to breast cancer screening and their demographic characteristics. Conclusion: The present study concluded that majority teacher training students are having average knowledge regarding breast cancer screening and suggesting to conduct the educational programme to enhance the knowledge of teacher training students who are playing an important role in the field of education.
Keywords: Breast cancer screening; education; proliferation of cells; teacher training students